HUBUNGAN USIA, PARITAS, DAN MENARCHE DINI DENGAN EKSPRESI MOLEKULER ESTROGEN RESEPTOR (ER) PADA PASIEN KARSINOMA MAMMAE DI RSPAD GATOT SOEBROTO TAHUN 2021 - Rizan Zakia (2023)
Breast cancer still become a cancer with the most cases among women according to GLOBOCON, 2020. Breast cancer is a hormone-dependent carcinoma which growth strongly influenced by hormonal status, especially estrogen. There are various risk factors that affect hormonal status, including age, parity, and early menarche. High estrogen exposure is associated with positive Estrogen Receptor (ER) expression on immunohistochemical examination. ER is an important biomarker to determine the choice of therapy and patient prognosis. The purpose of this study was to determine the correlation between age, parity, and early menarche with Estrogen Receptor (ER) expression. A retrospective cohort was used with secondary medical record within 133 patients diagnosed with breast cancer at Gatot Soebroto Army Hospital. The results showed that patients were aged > 40 years (88%), had a history of parity (81.2%), and history of early menarche (46.6%). The majority of the immunohistochemical examination results were ER (+) (82%) and Luminal molecular subtype (73,6%). Bivariate analysis using Fisher's exact test illustrates that there is a significant relationship between age (p-value = 0.000, RR=1.99, 95% CI=1.14 - 2.49) and parity (p-value = 0.001, RR=1 .57, 95% CI=1.10 - 2.24) with ER expression. Chi-Square test on early menarche shows that there is a significant correlation between early menarche and ER expression (p-value = 0.005, RR = 1.25, 95% CI=1.07 - 1.47=). The results of multivariate analysis showed that age (p-value=0,001, OR=7,43, 95% CI =2,32 - 23,82) has the most correlation with the expression of ER. It can be concluded that age and early menarche are positively related to ER expression (+).